1992
DOI: 10.1002/pd.1970121005
|View full text |Cite
|
Sign up to set email alerts
|

Second‐trimester maternal serum immunoreactive inhibin as a marker for fetal Down's syndrome

Abstract: We measured immunoreactive inhibin in the maternal serum of 80 pregnancies with a chromosomally normal fetus and ten Down's syndrome pregnancies in the second trimester. The inhibin level in all Down's syndrome pregnancies was above the normal median; the multiple of the normal median (MoM) was 1.9. We found a statistically significant difference between the levels of inhibin in unaffected and affected pregnancies (Kolmogorov-Smirnov test: p < 0.002). Using an arbitrarily chosen cut-off of 2.4 MoM, 40 per cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
1

Year Published

1995
1995
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(49 citation statements)
references
References 18 publications
1
47
0
1
Order By: Relevance
“…The median MOM value in our large Down's series was lower than that noted in a small preliminary series (Spencer et al, 1993b) using a nonspecific inhibin assay (1-77 vs. 3.60) but higher than noted by Cuckle et al (1994) using the same non-specific assay (1 '3) and closely similar to that initially published by Van Lith et al (1992), again using the same non-specific assay (1.9). Doubts have already been expressed about the contribution of the non-specific inhibin assay to the wide variation of results between these three studies (Cuckle et al, 1994).…”
Section: Resultssupporting
confidence: 76%
“…The median MOM value in our large Down's series was lower than that noted in a small preliminary series (Spencer et al, 1993b) using a nonspecific inhibin assay (1-77 vs. 3.60) but higher than noted by Cuckle et al (1994) using the same non-specific assay (1 '3) and closely similar to that initially published by Van Lith et al (1992), again using the same non-specific assay (1.9). Doubts have already been expressed about the contribution of the non-specific inhibin assay to the wide variation of results between these three studies (Cuckle et al, 1994).…”
Section: Resultssupporting
confidence: 76%
“…Van Lith et al (254) reported that immunoreactive inhibin levels in maternal serum were significantly higher in all ten tested pregnant women with fetuses of Down's syndrome, compared with those in normal pregnancies in the second trimester. Although the mechanism for the increased inhibin in maternal serum of women bearing these chromosomally abnormal fetuses is unknown, their observations clearly indicate that inhibin may be used as a marker, in combination with AFP, UE, and |3-hCG, in screening for fetal Down's syndrome (254). However, Cuckle et al (255) found only a relatively small elevation of inhibin levels in maternal serum in 19 pregnancies affected by fetal Down's syndrome, indicating the limited value of inhibin measurement in maternal screening for fetal Down's syndrome.…”
Section: Fetal Down's Syndromementioning
confidence: 97%
“…Nonspecific assays that cannot distinguish between these forms of inhibin were often used in the early reports of the association between inhibin and Down's syndrome in the second trimester. [12][13][14] Monoclonal assays can now selectively measure the various inhibin precursors and the two dimeric inhibins. The assay that selectively measures dimeric inhibin A is more discriminatory for Down's syndrome in the second trimester than the non-specific assays.…”
mentioning
confidence: 99%